+0  
 
0
329
2
avatar+587 

Solve the system of equations. Show your work.

y = x- 3x + 4 

x + y = 4

 

Answer:

 Feb 27, 2018
 #1
avatar+111395 
+2

y = x^2 -3x + 4      (1)

x + y  = 4  ⇒   y  = 4 - x    (2)

 

Sub (2)  into (1)

 

4 - x  =  x^2  - 3x + 4       subtract 4 from both sides

 

-x = x^2 - 3x       add x to both sides

 

x^2 - 2x  = 0   factor

 

x( x - 2)  =  0

 

Set each factor to 0 and solve for x and we get that

 

x =  0   or x  = 2

 

When x = 0.....y  =  4 - 0  =    4      ⇒   (0, 4)

 

When x  =  2.....y  =  4 -  2   =  2  ⇒    (2 , 2)

 

 

cool cool cool

 Feb 27, 2018
 #2
avatar+587 
+1

thank you so much!

adore.nuk  Feb 27, 2018

14 Online Users

avatar
avatar